2001
DOI: 10.1152/ajprenal.2001.281.4.f693
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin impairs recovery from acute renal failure: role of cell-cycle arrest and apoptosis of tubular cells

Abstract: The immunosuppressive effect of rapamycin is mediated by inhibition of interleukin-2-stimulated T cell proliferation. We report for the first time that rapamycin also inhibits growth factor-induced proliferation of cultured mouse proximal tubular (MPT; IC(50) ~1 ng/ml) cells and promotes apoptosis of these cells by impairing the survival effects of the same growth factors. On the basis of these in vitro data, we tested the hypothesis that rapamycin would impair recovery of renal function after ischemic acute r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
204
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(228 citation statements)
references
References 45 publications
(74 reference statements)
21
204
1
2
Order By: Relevance
“…The anti-proliferative effect of sirolimus has also been observed in smooth muscle cells, resulting in potent inhibition of neointimal proliferation after balloon-induced vascular injury in animal models (26,27). Interestingly, a recent report strongly suggests that sirolimus may exert a similar anti-proliferative effect in renal tubular cells (28). The authors suggest that 'the combined effects of increased tubular cell loss (via apoptosis) and profound inhibition of the regenerative response of tubular cells' together delayed recovery from ischemia-induced acute renal failure.…”
Section: Discussionmentioning
confidence: 98%
“…The anti-proliferative effect of sirolimus has also been observed in smooth muscle cells, resulting in potent inhibition of neointimal proliferation after balloon-induced vascular injury in animal models (26,27). Interestingly, a recent report strongly suggests that sirolimus may exert a similar anti-proliferative effect in renal tubular cells (28). The authors suggest that 'the combined effects of increased tubular cell loss (via apoptosis) and profound inhibition of the regenerative response of tubular cells' together delayed recovery from ischemia-induced acute renal failure.…”
Section: Discussionmentioning
confidence: 98%
“…It is increasingly important to comprehensively understand the role of mTORC1 in acute injury, because adverse clinical effects have been reported associated with sirolimus therapy, especially in the case of lung transplants (25,45,46). In the studies based on animal models, rapamycin treatment has been demonstrated to result in acute renal failure, liver regeneration, and lung injury (39,47,48). In the current study, we demonstrated the positive contribution of mTORC1-mediated S6K1-Stat3 activation in colon tissues toward recovery from acute experimental colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental mesangial proliferative glomerulonephritis and acute renal failure, mTOR inhibitors have been shown to cause inflammation and apoptosis. 60,61 Myocardial infarctions have also been noted. 62 Second, cardiomyocytes have high need for oxygen provided by blood vessels.…”
Section: Discussionmentioning
confidence: 99%